MANAGEMENT OF COGNITIVE LOAD ON STUDENT’S MATHEMATICAL PROFICIENCY AT SMP NEGERI 20 KOTA SERANG - Waluyo, Binsar; Hendrayana, Aan (Universitas Muhammadiyah Makassar, 2024)
This research is motivated by the fact that the level of conceptual understanding in Indonesia is still relatively low. The low level of conceptual understanding is related to how students manage and process the information received when they studying material, considering cognitive load. Learning with attention to cognitive load is believed to enhance students' mathematical conceptual understanding. The research aims to determine whether students' mathematical conceptual understanding with cognitive load-aware learning is better than students with conventional learning, both in terms of initial ability and not. The method used in this research is a mixed-method with a sequential explanatory design. Research instruments consist of test and non-test instruments. Data were obtained from initial ability tests and conceptual understanding as test instruments and questionnaires, interviews, and documentation as non-test instruments. The results show that students' mathematical conceptual understanding with cognitive load-aware learning is better than students with conventional learning, both in terms of initial ability and not. The conclusion of the research is that the treatments given to both classes overall have yielded quite positive results in students' mathematical conceptual understanding. However, the comparison between students who received cognitive load-aware learning and those who received conventional learning shows a significant difference.